2013
DOI: 10.1371/journal.pone.0069065
|View full text |Cite
|
Sign up to set email alerts
|

Climate Control on Tree Growth at the Upper and Lower Treelines: A Case Study in the Qilian Mountains, Tibetan Plateau

Abstract: It is generally hypothesized that tree growth at the upper treeline is normally controlled by temperature while that at the lower treeline is precipitation limited. However, uniform patterns of inter-annual ring-width variations along altitudinal gradients are also observed in some situations. How changing elevation influences tree growth in the cold and arid Qilian Mountains, on the northeastern Tibetan Plateau, is of considerable interest because of the sensitivity of the region’s local climate to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 64 publications
8
32
1
1
Order By: Relevance
“…The interpretation of a dominant moisture control on tree growth in this region is supported by a number of previous studies (16,(19)(20)(21)(22). Interpreting local tree growth for this species as a predominant response to interannual variability of prior July to current-year June precipitation is consistent with the results of refs.…”
Section: Climatic Interpretation and Reconstructionsupporting
confidence: 52%
“…The interpretation of a dominant moisture control on tree growth in this region is supported by a number of previous studies (16,(19)(20)(21)(22). Interpreting local tree growth for this species as a predominant response to interannual variability of prior July to current-year June precipitation is consistent with the results of refs.…”
Section: Climatic Interpretation and Reconstructionsupporting
confidence: 52%
“…In contrast, the present study found consistent patterns of Qilian juniper growth at the high-and low-elevation sites. Consistent growth at high-and low-elevation sites has been reported in other parts of the Qinghai-Tibetan Plateau (Gao et al 2013;Yang et al 2013). Water stress was the main climatic factor that caused homogeneous tree growth across an altitudinal gradient in the western of the Qilian Mountains .…”
Section: Discussionsupporting
confidence: 67%
“…Another recent study examined samples of Qilian junipers also in the Qilan Mountains of the northeastern Tibetan Plateau (Gao et al 2013). Instead of sampling sites with broad elevation ranges as in He et al (2013) and Yang et al (2013), they sampled in four narrow elevation zones of 20-40 m on a single slope ranging from 3200 to 3600 m. Their results did not show general trends of decreased sensitivity of tree growth to precipitation and increased sensitivity to temperature as elevation increases.…”
Section: Introductionmentioning
confidence: 97%
“…They concluded that elevation has no significant effects on tree growth. Similarly, Yang et al (2013) sampled Qilian junipers (Sabina przewalskii Kom.) at four sites on a mountain slope, from the lower-to upper-treeline in the semi-arid Qilian Mountains area, and found that precipitation remained the major limiting factor of tree growth for all sites within the elevation range from 3000 to 3520 m a.s.l.…”
Section: Introductionmentioning
confidence: 99%